The Influence of the Stem-Based Guided Inquiry Model on Students’ Creative Thinking Skills in Science Learning: A Meta-Analysis Study - Dewanto Dewanto; Tomi Apra Santosa; Arista Ratih; Asrizal Asrizal; Hardeli Hardeli (Postgraduate, University of Mataram, 2024)
This study aims to determine the effect of STEM-based guided inquiry models on students' Creative Thinking Skills in science learning. This type of research is a meta-analysis. The study analyzed 15 primary studies published in 2018-2023 that had met the inclusion criteria. Search data sources through the Google scholar database; ERIC, Taylor of Francis, ScienceDirect and ProQuest. Data analysis with the help of the JSAP application verse 0.16.3. These results conclude that the overall value of effect size is 0.99 (95% CI [ 0.79; 1,19]) high category. These findings show that the application of STEM-based inquiry-based learning models affects students' 21st century thinking skills. In addition, these findings provide important information on STEM-based guided inquiry learning in schools.